2018
DOI: 10.1002/em.22216
|View full text |Cite
|
Sign up to set email alerts
|

Genomic chaos in peripheral blood lymphocytes of Hodgkin's lymphoma patients one year after ABVD chemotherapy/radiotherapy

Abstract: Hodgkin's lymphoma (HL) is a lymphoid malignancy representing 5% of all cancers in children, 16% in adolescents, and 30-40% of all malignant lymphomas and has a survival rate of ~95% at 10 years. One of the most common treatment schemes uses a cocktail of genotoxic agents including adriamycin, bleomycin, vinblastine, and dacarbazine (ABVD) with or without radiotherapy. We investigated the occurrence of chromosomal damage in peripheral blood lymphocytes from five patients diagnosed with HL who provided samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Liu et al [31], found that when treating cells with chemotherapeutic agents such as those used in these patients, doxorubicin (Adriamycin) and alkylating agents, although there is a high frequency of cell death during stress, some of the chaotic genomes can survive and continue to change until the surviving genomes are selected. In fact, the observations made by Ramos et al [32], and Salas et al [17], resemble the pattern proposed by the in vitro experiments of Liu et al [31] in 2014:…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Liu et al [31], found that when treating cells with chemotherapeutic agents such as those used in these patients, doxorubicin (Adriamycin) and alkylating agents, although there is a high frequency of cell death during stress, some of the chaotic genomes can survive and continue to change until the surviving genomes are selected. In fact, the observations made by Ramos et al [32], and Salas et al [17], resemble the pattern proposed by the in vitro experiments of Liu et al [31] in 2014:…”
Section: Discussionsupporting
confidence: 78%
“…It is possible that not quantifying this type of alterations, may be the reason for some unexpected data in the study conducted by Ramos et al [32], where a smaller number of classical cytogenetic alterations were found during-treatment, as compared with post-treatment samples. Duringtreatment samples represent the moment when all the cells of the whole organism were under stress, and it is during this moment when according with the results of Liu et al [31], the non-classical genomic damage could be present in a significantly high proportion, and a fraction of the highly rearranged and chaotic karyotypes could be eliminated.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, we found a significant increase of chromosomal aberrations (CAs) and cells with genomic chaos 1 year after treatment and we concluded that these effects were due to the genotoxicity of the chemical and physical agents used in the anticancer therapy. The authors of the letter to the editor, while supporting our main finding, assert that that these observations are due to the reactivation of preexisting virus in the lymphocytes of the HL patients.In Ramos et al (Ramos et al 2018) the frequencies of NCCA observed in the HL samples were significantly higher than in the control samples at all three sampling times investigated: beforetreatment, during-treatment, and 1-year after treatment with ABVD (Adriamycin, Bleomycin, Vinblastine, and Dacarbazine)/ radiotherapy. Although in the study of M' Kacher et al (2003), analyses were conducted at five time points, three of these time points overlap with ours.…”
mentioning
confidence: 82%
“…In Ramos et al (Ramos et al 2018) the frequencies of NCCA observed in the HL samples were significantly higher than in the control samples at all three sampling times investigated: beforetreatment, during-treatment, and 1-year after treatment with ABVD (Adriamycin, Bleomycin, Vinblastine, and Dacarbazine)/ radiotherapy. Although in the study of M' Kacher et al (2003), analyses were conducted at five time points, three of these time points overlap with ours.…”
mentioning
confidence: 82%
“…Ramos et al (Ramos et al ) have reported an increase of chromosomal aberrations in peripheral blood lymphocytes in HL patients 1 year after treatment as compared to that observed before and during chemotherapy. Interestingly, the authors identify the presence of cells with a high frequency of chromosomal aberrations in three out of five patients (more than 10 aberrations per cell).…”
mentioning
confidence: 95%